Computational Statistics and Mathematical Modeling Methods in Intelligent Systems Proceedings of 3rd Computational Methods in Systems and Software 2019, Vol. 2 - Silhavy, Radek; Silhavy, Petr; Prokopova, Zdenka (Advances in Intelligent Systems and Computing,, 2019)
This book presents real-world problems and exploratory research in computational statistics, mathematical modeling, artificial intelligence and software engineering in the context of the intelligent systems. This book constitutes the refereed proceedings of the 3rd Computational Methods in Systems and Software 2019 (CoMeSySo 2019), a groundbreaking online conference that provides an international forum for discussing the latest high-quality research results.